Socioeconomic Determinants of Stunting Among Toddlers in the Working Area of Tarus Health Center, Kupang Regency - Lay Djara, Desi Darmiati; Marni, Marni; Oematan, Grouse (Faculty of Public Health, Nusa Cendana University, 2024)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake over a prolonged period due to improper feeding practices that do not meet nutritional needs. The percentage of stunted children at the Tarus Health Center has increased every year from 2019 to 2022. This study aims to determine the socioeconomic factors associated with stunting among children under five in the working area of Tarus Health Center, Kupang Regency. This type of research is an analytical survey with a case-control study design. The sample consisted of 36 cases and 36 controls, selected using probability sampling techniques. Data collection was carried out through observation and structured interviews using questionnaires. Data analysis included univariate and bivariate analysis using the chi-square test. The results showed that the factors associated with stunting were family income (p-value = 0.023) and history of infectious diseases (p-value = 0.001), while factors not associated were maternal education (p-value = 0.617) and maternal occupation (p-value = 0.629). Based on these findings, it is expected that health workers provide education on proper dietary practices by utilizing local resources, and the government should also create adequate job opportunities so that human resources can improve, thereby reducing stunting rates in families.